Context Matters: Distinct Disease Outcomes as a Result of Crebbp Hemizygosity in Different Mouse Bone Marrow Compartments. - Ting Zhou (PLoS ONE, 2016)
Perturbations in CREB binding protein (CREBBP) are associated with hematopoietic malignancies, including myelodysplastic syndrome (MDS). Mice hemizygous for Crebbp develop myelodysplasia with proliferative features, reminiscent of human MDS/myeloproliferative neoplasm-unclassifiable (MDS/MPN-U), and a proportion goes on to develop acute myeloid leukemia (AML). We have also shown that the Crebbp+/- non-hematopoietic bone marrow microenvironment induces excessive myeloproliferation of wild-type cells. We now report that transplantation of unfractionated Crebbp+/- bone marrow into wild-type recipients resulted in either early-onset AML or late-onset MDS and MDS/MPN-U. In contrast, purified Lin-Sca-1+c-Kit++ cells primarily gave rise to MDS with occasional transformation to AML. Furthermore, Crebbp+/- common myeloid progenitors and granulocyte/macrophage progenitors could trigger skewed myelopoiesis, myelodysplasia and late-onset AML. Surprisingly, the phenotypically abnormal cells were all of wild-type origin. MDS, MPN and AML can thus all be transferred from Crebbp+/- BM to wild-type hosts but fractionated bone marrow does not recapitulate the full disease spectrum of whole bone marrow, indicating that not only mutational status but also cellular context contribute to disease outcome. This has important consequences for structuring and interpreting future investigations into the underlying mechanisms of myeloid malignancies as well as for their treatment.